LEKSIKON TANAMAN PADA BONEKA PETRA DALAM RITUAL KEMATIAN MASYARAKAT TENGGER SEBAGAI SIMBOL LELUHUR: KAJIAN ANTROPOLINGUISTIK - Firdaus, Elvin Nuril; Kriswanto, Muhammad; Padang, Naomi Baso; Saputra, Kelfin Jaya; Arifin, Nur Hikmah; Fatmawati, Galuh; Ardhian, Dany (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
Petra is one of the ritual dolls used by the Tenggerese people. Petra is generally used in funeral ceremonies as a symbol of ancestral spirits or people who have died, so petra is a doll that is respected by the local community. This study focuses on examining the plant lexicon that composes Petra dolls. This research was conducted to increase the understanding of the local community about the dolls commonly used in rituals as a symbol of the ancestors and to examine the possibility of inter-language contact. This research was conducted in Tengger Village using a qualitative descriptive approach with observation and interview data collection methods. Sources of data were obtained from traditional healers and Pak Sepuh. Data analysis used lexical semantic analysis. The results of this study show the lexicon of the plants that make up the petra doll; the meaning indicated; and petra as a marker of ancestral identity. Petra is made from selected plants that grow in the Tengger region and become a medium for ancestral spirits in funeral ceremonies. Therefore, Petra is a form of respect for the local community towards their ancestors until now. Keywords: Petra Doll, Lexicon, Tengger, Antropolinguistic, Lexicon Semantics